Influence of Substrate Position on the Microstructure and Mechanical Properties of CrN Coating Prepared by Closed Magnetron Sputtering - YE Yan, BAO Ming - dong (Cailiao Baohu, 2022)
In order to obtain excellent properties of CrN coating, the CrN coating was prepared by closed unbalanced magnetron sputtering with substrate locating in different positions (one - axis, three - axis) in the system to study the effects of substrate position on the microstructure and mechanical properties of the coating. Results showed that the positions of substrate and target had no effect on the phase composition of the CrN coating, which all turned out to be CrN (111), CrN (200), and CrN (220) crystal planes. The CrN coating prepared on one - axis possessed smaller grain size, low density, thickness of about 3.2 μm, coating - substrate binding force of HF4, more impurity phase of Cr2N, and friction coefficient of 0.725～0.975, while the CrN coating prepared on three - axis had larger grain size, high density, thickness of about 2.2 μm, coating - substrate binding force of HF1, less impurity phase of Cr2N, and friction coefficient of 0.525～0.700.